Transparent composites prepared from bacterial cellulose and castor oil based polyurethane as substrates for flexible OLEDs. Issue 44 (30th September 2015) - Pinto, E. R. P.; Barud, H. S.; Silva, R. R.; Palmieri, M.; Polito, W. L.; Calil, V. L.; Cremona, M.; Ribeiro, S. J. L.; Messaddeq, Y.
Abstract : Flexible and transparent BC/PU composites were prepared, which exhibit excellent transparency (up to 90%) in the visible region and great mechanical properties, with a tensile strength of up to 69 MPa and a Young's modulus of up to 6 GPa. Abstract : Flexible and transparent composites were prepared from bacterial cellulose (BC) and castor oil based polyurethane (PU). The new BC/PU composites exhibit excellent transparency (up to 90%) in the visible region and great mechanical properties, with a tensile strength of up to 69 MPa and a Young's Modulus up to 6 GPa. The resulting free-standing thin films possessed low surface roughness (below 1 nm), and whose properties suggest a potential candidate substrate for flexible light emitting devices. Subsequently, the fabrication of flexible organic light emitting diodes (flexible OLEDs) was successfully investigated by using flexible transparent BC/PU membranes rather than standard flat glass substrates.